The University of the Third Age as an institution counteracting marginalization of older people - Marcinkiewicz, Aleksandra (Journal of Education Culture and Society, 2020)
The article presents the role of the University of the Third Age in counteracting the effects of marginalization of the elderly. The history of the University of the Third Age is presented and also different models of this institution are characterized. The paper presents new trends in research conducted by participants of the U3A and shown their relation to marginalization.